Types of Speech Functions Used by Online Shopping Frauds - Yolla . Wulandari; Rahmad . Husein; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2021)
In today’s world, shopping on Instagram is quickly becoming the preferred way for consumers to not only learn about new brands and products on Instagram, but also purchase them in just a few simple steps.One of the top issues of online shopping is its security concerns.Online shopping fraud is one of a cybercrime which often occurs lately.  Fraudsters usually manipulate their victims through their language used. In order to manipulate their victim, a fraud should be able to use the speech function or linguistic function in the proper context of conversation to build trust of their victim. This study was aimed at investigating the speech function used by online shopping frauds on Instagram. This research was conducted in a qualitative research. The data were clauses consist of speech functions used by online shopping frauds on instagram. Five chats of online shopping fraudsters with their victims taken from Indonesia Online Shop Blacklist has taken as data sources by using purposive sampling. In order to identify the types of speech functions used by the fraudster, Halliday’s theory of Interpersonal Function was used. The findings showed that the types of speech functions found used by online shopping frauds in instagram are statement, question, command, and minor.  In which statement is more often used by fraudster in instagram, followed by command, question and minor. It indicates that the fraudster use statement for giving information about the product which they sell, they also tend to use statement to answer the questions from the consumer about their product, delivery process, payment method, etc.Keywords: Speech Functions, Fraudster, Instagram, Online Shopping, Discourse